Dampak Referendum Brexit Terhadap Kebijakan Imigran Uni Eropa di Inggris - Pratama Putra, I Dewa Gede Prastha; Susanti, Sukma; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT This research analyzes how the UK’s policy plan decides on Immigrant Policy after the Brexit Referendum in 2016. The UK’s decision plan will be analyzed using Immigrant Theory, Regionalism and Foreign Policy. This discussion aims to see a picture of how immigrants policy plans are after the UK decides to leave the European Union through the referendum. Immigrant theory is used to analyze problems caused by the presence of immigrants in a country. Regionalism concept is used to observe European Union organizations in a skeptical perspective that caused UK’s renounce their membership in the European Union. Foreign Policy Concept is used to explain that the Immigrant Uni Eropa has become the motivation for the UK to leave European Union through Brexit Referendum. The final result of the UK’s plans to adopt Australian policy on conducting selection to the entry of EU and non-EU immigrants. Keywords: Brexit, Immigrant, Europe Union, United Kingdom.